Approaches on firm valuation - Magni, Carlo Alberto; Malagoli, Stefano (Managerial finance, 2007)
This ebook discusses various approaches to firm valuation relating to issues such as valuation by cash flow discounting, strategic options on valuations and information transparency. Specifically, it also looks at SFAS 142 and the use of fuzzy logic and expert systems.